APPLICATION OF THE HESS-MARCEAU BILIOPANCREATIC DIVERSION PROCEDURE IN THE TREATMENT OF MORBID OBESITY (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
The paper presents material on the problem of surgical treatment of patients with severe forms of obesity. Based on factual material, an assessment is given of the methods of combined bariatric operations used by the authors.